2021
DOI: 10.3390/pharmaceutics13071029
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Drawn Syringes of Comirnaty for an Efficient COVID-19 Mass Vaccination: Demonstration of Stability

Abstract: Moving towards a real mass vaccination in the context of COVID-19, healthcare professionals are required to face some criticisms due to limited data on the stability of a mRNA-based vaccine (Pfizer-BioNTech COVID-19 Vaccine in the US or Comirnaty in EU) as a dose in a 1 mL-syringe. The stability of the lipid nanoparticles and the encapsulated mRNA was evaluated in a “real-life” scenario. Specifically, we investigated the effects of different storing materials (e.g., syringes vs. glass vials), as well as of tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 10 publications
4
10
0
Order By: Relevance
“…Vortex mixing is a common operation in the laboratory; however, it should be avoided or kept as brief as possible. Selmin et al reported that strong mechanical stress, such as vortexing, leads to LNP aggregation and degradation of the enclosed mRNA [25], which is consistent with the results of this study. In addition, the possibility of aggregation was examined by collecting from a vial; however, the physicochemical properties and biological activity of LNP did not change each time when collected from the same vial on five separate occasions (Figure 5).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Vortex mixing is a common operation in the laboratory; however, it should be avoided or kept as brief as possible. Selmin et al reported that strong mechanical stress, such as vortexing, leads to LNP aggregation and degradation of the enclosed mRNA [25], which is consistent with the results of this study. In addition, the possibility of aggregation was examined by collecting from a vial; however, the physicochemical properties and biological activity of LNP did not change each time when collected from the same vial on five separate occasions (Figure 5).…”
Section: Discussionsupporting
confidence: 93%
“…Salmin et al reported that mRNA-LNPs aspirated in syringes maintained their physicochemical properties for about a day, independent of syringe material, but the strong mechanical stress of manually pumping 40 times resulted in particle aggregation [25]. We prepared our experiment to determine whether LNPs could aggregate due to aspiration pressure, as they were collected from the vial through a syringe needle.…”
Section: The Suction Pressure From Vials Did Not Affect the Stability...mentioning
confidence: 99%
“…This profile indicates that particle physical stability is not a major risk when a chemically stable API is used. However, the internal structure of mRNA containing particles is different from those containing siRNA 7 and mRNA-LNP particles are more likely to disintegrate upon mechanical stress, such as shaking and dropping of vials 91 , 92 . Another example is the formation of layers of aggregates on filter surfaces during sterile filtration 93 .…”
Section: Attributes Specific To the Lnp Formulationmentioning
confidence: 99%
“…Two studies on real-life in-use stability of mRNA-LNP DP have been published. First, the stability of mRNA-LNPs during storage between being drawn into of syringes and being injected was monitored 92 . The second study looked at the stability of left-over material in vials of Comirnaty 91 .…”
Section: Real-life Experience With In-use Stability Of Mrna-lnpsmentioning
confidence: 99%
See 1 more Smart Citation